Leukaemia Presenting with Nasal Septal Abscess: A Case Report - Aishwarya Biradar; Ruchir Dashora; Mayur H Ingale; Vinod Shinde; Paresh Chavan (Journal of Clinical and Diagnostic Research)
Nasal Septal Abscess (NSA) is a rare but serious condition that typically arises from trauma, infections, or surgical interventions. However, in immunocompromised patients, NSA may develop spontaneously due to underlying haematological conditions. A 28-year-old male with recently diagnosed pre-B-cell Acute Lymphoblastic Leukaemia (ALL) presented with bilateral nasal obstruction and respiratory discomfort. Examination and imaging confirmed an NSA with cartilage erosion. Initial management included aspiration and empirical antibiotic therapy. However, recurrence necessitated incision and drainage, with cultures revealing fungal elements, prompting antifungal treatment. The patient responded well to therapy and no long-term complications were observed. This case underscores the importance of recognising NSA as a potential complication in leukaemia patients, even in the absence of trauma. Timely diagnosis and appropriate management are critical in preventing complications such as nasal deformities and recurrent infections.